A Systematic Review of Differences Between Conventional Orthoses and 3D-Printed Orthoses - Rodrigues, Ana Cláudia Tavares [UNESP] (2021)
Rapid prototyping and 3D printing technologies have been innovative options for orthotic development, that are assistive devices applied to any part of the body to different disabilities or injuries. The aim of the study was to investigate scientific evidence about the effectiveness of using 3D printed orthoses in relation to conventional orthoses, through a systematic literature review in the years 2010 to 2020. Scientific evidence identifies that there are improvements associated with the development and use of rapid prototyped and 3D printed orthoses however the publications found present were small in sample sizes and lack comprehensive end-user evaluation.